The Relationship Between Crime and Electronic Gaming Expenditure: Evidence from Victoria, Australia - Wheeler, Sarah A. (Journal of quantitative criminology, 2011)
Gambling in Australia is a significant economic activity. Expenditure on its many forms is sizeable and has undergone sustained periods of expansion. At the same time, the structure of the gambling industry has undergone substantial change, with the use of gaming facilities in local hotels and licensed clubs now representing one of the most predominant forms of gambling. Despite this, and the extensive international literature on the relationships between gambling and crime, there have been relatively few studies which examine the local area effects of gaming establishments on crime in Australia. This study uses a unique set of data from the Australian state of Victoria, a region in which local area expansion of gaming networks has been considerable since 1991, to investigate the relationship between gaming machine expenditure and various types of crime in 1996, 2001 and 2006. One particular focus is that of income-generating crime, defined here as theft, fraud, breaking and entering, forgery, false pretences, larceny and robbery. After controlling for a host of statistical issues, our results indicate a consistent positive and significant relationship between gaming and crime rates, especially income-generating crime rates, at the local level.